2003
DOI: 10.1007/s00464-002-8822-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery for stage I colorectal cancer

Abstract: LS was shown to be technically feasible and oncologically sound for the treatment of patients with stage I colorectal cancer, and favorable short- and long-term outcomes were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Furthermore, most Japanese insurance plans cover the complete cost of hospitalization. As a result, neither patients nor surgeons are eager for early discharge [14].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most Japanese insurance plans cover the complete cost of hospitalization. As a result, neither patients nor surgeons are eager for early discharge [14].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 This procedure has several distinct advantages in comparison to open surgery, including briefer use of analgesics, earlier return of bowel motility, a shorter hospital stay, and faster perioperative recovery. 2,3 The metaanalysis of the results of 2512 procedures from 12 randomized clinical trials reported improved short-term outcomes for laparoscopic surgery in comparison to conventional open surgery for colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, this effect may be explained by the fact that surgical stress, which impairs immunity [27,28], is more intense following OC than LAC [29,30]; because the immunity plays a crucial role in tumor progression and metastatic spread [31,32]. Furthermore, the laparoscope, which utilizes a telescopic video camera, usually gives the surgeons a better, magnified view of the internal organs than may be achieved by the unaided eye during traditional OC [33,34].…”
Section: Discussionmentioning
confidence: 95%